Effects of hyperprolactinemia and ovariectomy on the tibial epiphyseal growth plate and bone formation in mice - Roberta Bastos Wolff (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2014)
PURPOSE: To evaluate the effects of ovariectomy and the hyperprolactinemia procedure in the tibial epiphyseal growth plate of female mice.METHODS: In this study, the epiphyseal growth plate of ovariectomized (OVX) and/or rendered hyperprolactinemic female mice by 50 days of treatment with 200 μg metoclopramide (M) was evaluated morphologically, morphometrically and immuno-histochemically. Forty female and adult mice were divided into four groups according to treatment: V group - animals treated with saline solution; H group - hyperprolactinemic animals; Ovx/V group - ovariectomized animals and treated with saline solution; Ovx/H group - hyperprolactinemic and ovariectomized animals. After the treatment period, the animals were sacrificed, tibia was removed and fixed in 10% buffered formalin and decalcified in 10% formic acid. The material was immersed in paraffin and subjected to histological processing in paraffin. The sections were stained with Masson's trichrome and immunohistochemistry was carried out for the pro-apoptotic protein BCL-2. The images for the morphological and morphometric study were analyzed with the imaging program AxioVision 4.8 (Carl-Zeiss(r), Germany).RESULTS: The combination of hyperprolactinemia and the ovariectomy procedure decreased the number of resting chondrocytes 1.5-fold, the number of proliferative chondrocytes 1.8-fold; the percentage of resting cartilage 2.4-fold and the percentage of trabecular bone 2.1-fold, compared with respective control animals.CONCLUSION: The procedure of ovariectomy combined with the metoclopramide-induced hyperprolactinemia in female mice has showed marked bone degeneration due to significant decrease of cell proliferation in the epiphyseal growth plate and bone formation.